2000
DOI: 10.1016/s0022-5223(00)70017-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular endothelial growth factor and vascular endothelial growth factor–c and decreased nm23 expression associated with microdissemination in the lymph nodes in stage i non–small cell lung cancer

Abstract: All of these findings lead us to conclude that the microspread of tumor cells in nodes detected by immunohistochemical anticytokeratin staining is definitely a metastasis with a high risk of systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 31 publications
5
66
2
Order By: Relevance
“…Three studies reported positive associations of tumor-cell VEGF-C status with nodal metastasis in NSCLCs 17,18 and micrometastasis in Stage I NSCLCs. 19 In contrast, three studies described no association of tumor-cell VEGF-C status with nodal metastasis in NSCLCs. 20 -22 Unlike the current study, Su and coworkers 32 reported that lung adenocarcinoma patients with high expression of tumor-cell VEGF-C were more likely than those with lower expression to have metastasis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Three studies reported positive associations of tumor-cell VEGF-C status with nodal metastasis in NSCLCs 17,18 and micrometastasis in Stage I NSCLCs. 19 In contrast, three studies described no association of tumor-cell VEGF-C status with nodal metastasis in NSCLCs. 20 -22 Unlike the current study, Su and coworkers 32 reported that lung adenocarcinoma patients with high expression of tumor-cell VEGF-C were more likely than those with lower expression to have metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported VEGF-C expression in NSCLCs. [17][18][19][20][21][22] In addition, NSCLC patients with nodal metastasis revealed higher serum VEGF-C levels than those without. 31 However, the association of tumor-cell VEGF-C and nodal metastasis in NSCLCs is still debated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the hematoxylin and eosin-stained slides of the tumor specimens, we selected blocks of the invasive edge in the tumor area. Paraffin-embedded tumor tissues were cut into consecutive sections 4 µm thick, deparaffinized, and subjected to immunohistochemical staining using the labeled streptavidin-biotin method, as described previously [14]. The primary antibodies used in the present study were a rabbit polyclonal antibody to angiostatin (Oncogene Research Products, Cambridge, MA) diluted 150-fold [15], a rabbit polyclonal antibody to endostatin (Lab Vision Corp., Fremont, CA), and a rabbit polyclonal antibody to VEGF (Santa Cruz Biotechnology Inc., Santa Cruz, CA) diluted 5 100-fold.…”
Section: Patientsmentioning
confidence: 99%